2017
DOI: 10.1055/s-0043-118127
|View full text |Cite
|
Sign up to set email alerts
|

CT and MRI Techniques for Imaging Around Orthopedic Hardware

Abstract: ZUSAMMENFASSUNGOrthopädische Implantate verringern die Bildqualität in der Schnittbildgebung. Bei steigendem Einsatz von orthopädi-schen Implantaten in einer alternden Bevölkerung ist eine Metallartefaktreduktion von zunehmender Bedeutung. Im folgenden Review möchten wir einen Überblick über die wesentlichen Artefakte in der Computertomografie und Magnetresonanztomografie sowie die neuesten Standards zur Verbesserung der Bildqualität geben. Alle Schritte der Bildakquisition von Gerätewahl über Scanvorbereitung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 43 publications
(40 reference statements)
1
58
0
Order By: Relevance
“…As a drawback of iMAR, the occurrence of new artifacts must be considered. Different studies have addressed this phenomenon, and the final conclusions were quite consistent: because the advantages of iMAR outweigh its disadvantages resulting in better visualization of anatomy and better conspicuity of anatomical abnormalities, the algorithm is ready for implementation in the clinical workflow [5,17,18,31]. It is worth noting that in this study, the new artifacts were not observed at the antenna tip or in the liver in extension of the antenna in the puncture direction, in other words, in the region of greatest interest.…”
Section: Discussionmentioning
confidence: 91%
“…As a drawback of iMAR, the occurrence of new artifacts must be considered. Different studies have addressed this phenomenon, and the final conclusions were quite consistent: because the advantages of iMAR outweigh its disadvantages resulting in better visualization of anatomy and better conspicuity of anatomical abnormalities, the algorithm is ready for implementation in the clinical workflow [5,17,18,31]. It is worth noting that in this study, the new artifacts were not observed at the antenna tip or in the liver in extension of the antenna in the puncture direction, in other words, in the region of greatest interest.…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, we investigated in this study TSE with high bandwidth optimization and STIR WARP sequences which are known to have reasonable acquisition times. However, it remains unknown if sensitivity and specificity of MRI for detecting screw loosening would be improved using sequences with more acquisition time such as SEMAC or MAVRIC [20,22,23,25,34].…”
Section: Discussionmentioning
confidence: 99%
“…Biomaterial advancements have led to the development of a hybrid implant comprised of a titanium base and a polymer top layer with an elastic modulus much more similar to the modulus of cartilage (Nathwani et al, 2017). However, the metal base still leads to scattering on computed tomography (CT) and magnetic resonance imaging (MRI) (Do, Sutter, Skornitzke, & Weber, 2018). Future clinical decision making is thus impaired, which is of great concern in case of new traumatic knee injuries (Adelani et al, 2016) and routine clinical follow‐up of the knee joint.…”
Section: Introductionmentioning
confidence: 99%